2005
DOI: 10.1007/s00572-005-0349-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycotrophy of crops in rotation and soil amendment with peat influence the abundance and effectiveness of indigenous arbuscular mycorrhizal fungi in field soil

Abstract: Mycotrophy of previous crops has been shown to have an impact on arbuscular mycorrhizal fungi (AMF), and the growth and productivity of succeeding crops. We studied the impact of 3 years of cultivation of eight crops with different degrees of mycotrophy, including mycorrhizal (strawberry, rye, timothy, onion, caraway) and non-mycorrhizal (turnip rape, buckwheat, fiddleneck) hosts, as well as the impact of peat amendment, on the effectiveness, amount and diversity of indigenous AMF. A field experiment having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
6
27
1
3
Order By: Relevance
“…The creation of non-mycorrhizal controls through the chemical destruction of native AMF (Buttery et al 1988;Liu et al 2002Liu et al , 2003Gazey et al 2004) or their repression using non-host crops (Vestberg et al 2005), fallow (Abu-Zeyad et al 1999) in rotation, or deep tillage (Miller et al 1995;Kabir et al 1998;Drijber et al 2000;Miller 2000) have revealed that AMF influence crop development. Considering the profound influence of AMF on many aspects of plant physiology and the complexity of the soil system, it is virtually impossible to pinpoint the mechanisms responsible for the AMF effect in any particular case.…”
Section: The "Mycorrhizal Effects"mentioning
confidence: 99%
“…The creation of non-mycorrhizal controls through the chemical destruction of native AMF (Buttery et al 1988;Liu et al 2002Liu et al , 2003Gazey et al 2004) or their repression using non-host crops (Vestberg et al 2005), fallow (Abu-Zeyad et al 1999) in rotation, or deep tillage (Miller et al 1995;Kabir et al 1998;Drijber et al 2000;Miller 2000) have revealed that AMF influence crop development. Considering the profound influence of AMF on many aspects of plant physiology and the complexity of the soil system, it is virtually impossible to pinpoint the mechanisms responsible for the AMF effect in any particular case.…”
Section: The "Mycorrhizal Effects"mentioning
confidence: 99%
“…This decrease in diversity is attributed to a complex selective pressure of agricultural practices, such as ploughing, fertilization and fungicide application, on the AMF communities (Douds and Millner, 1999;Roldan et al, 2007). Besides agroecosystems plant species, soil types, weeds and previous crop have an effect on AMF population as well (Jansa et al, 2002;Mathimaran et al, 2005;Vestberg et al, 2005). Van der Heijden et al (1998) showed that both plant diversity and plant productivity rise with increasing diversity of mycorrhizal fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Estos compuestos poseen actividad biocida que incluye efectos fitotóxicos (Petersen et al, 2001), nematicidas (Henderson et al, 2009) y fungicidas (Dunne et al, 2003). Algunas investigaciones han informado que el sistema de cultivo y la rotación afectan las esporas y colonización de las raíces (Jeffries y Barea, 2001); pero, al incluir plantas hospederas en la rotación se pueden mantener las comunidades fúngicas con incremento en el rendimiento del cultivo siguiente (Vestberg et al, 2005).…”
Section: Crop Rotation System Using Oats (A-t) Lupin (L-t) and Rapesunclassified